Novel liquid crystalline organic semiconducting oligomers incorporating N-heterocyclic carbazole moieties for fluorescent OLEDs. Issue 11 (2nd September 2017) - Hu, Guang; Kitney, Stuart P.; Kelly, Stephen M.; Harrison, William; O'Neill, Mary
ABSTRACT: A novel class of nematic liquid crystalline organic semiconducting oligomers incorporating N -heterocyclic carbazole moieties has been synthesised using simple and highly efficient reaction pathways. The electroluminescent colour of these novel oligomers can be varied in a controlled manner by molecular design. The values of the ionisation potential and the electron affinity of these electroluminescent oligomers can also be matched by structural design to the Highest Occupied Molecular Orbital (HOMO) energy level of the electron-blocking layer and the Lowest Unoccupied Molecular Orbital (LUMO) energy level of electron-transporting layer in the Organic light emitting diodes to create low charge-injection barriers for electrons and holes, respectively leading to electroluminescence with an efficacy up to 4.1 cd A −1 . GRAPHICAL ABSTRACT: